Does relative deprivation condition the effects of social protection programs on political support? Experimental evidence from Pakistan - Kosec, Katrina; Mo, Cecilia Hyunjung (International Food Policy Research Institute, 2022)
2022 UPDATE: Could perceived relative economic standing affect citizens’ support for political leaders and institutions? We explore this question by examining Pakistan’s national unconditional cash transfer program, the Benazir Income Support Program (BISP). Leveraging a regression discontinuity approach using BISP’s administrative data and an original survey experiment, we find that perceptions of relative deprivation color citizen reactions to social protection. When citizens do not feel relatively deprived, receiving cash transfers has little sustained effect on individuals’ reported level of support for their political system and its leaders. However, when citizens feel relatively worse off, those receiving cash transfers become more politically satisfied, while those denied transfers become more politically disgruntled. Moreover, the magnitude of the reduction in political support among non-beneficiaries is larger than the magnitude of the increase in political support among beneficiaries. This has important implications for our understanding of the political ramifications of rising perceived inequality.